The answer is (34/11, -5/11).
First, let's rewrite the 2 equations:
![3a + 5b - 7 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ny8r83wv4c78koseycvm85cfom18nbm7j5.png)
![a - 2b - 4 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7rvkujdtg6u8r2itki7j0whmzio7tv3w20.png)
Then let's transform these 2 equations into the form ax+by=c
So that would be:
![3a + 5b = 7 \\ a - 2b = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2hgq9g1zvn7s0gmr7py2r86qi9i01wydw4.png)
Now our goal is to isolate one of the variables a or b. Lets pick a since its easier. To do this, multiply equation 2 by -3 so that 3a + -3a=0
![- 3a + 6b = - 12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8t2ythtk7b2kk4av77rkkw4ursuiexy7km.png)
Now add both equations together:
![\: \: \: \: 3a + 5b = 7 \\ + - 3a + 6b = - 12 \\ \: \: \: \: 11b = - 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eeilrmcbj76y3vh714weaf4tv1via5qj06.png)
Now to isolate b, divide both sides by 11
![b = - (5)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dhyime688gn5cbamho1hep5e2ckvx9qw9h.png)
Now we know the value of b, its time to solve for a
To do this, you substitute b in any equation to -5/11. In this case, I'll choose equation 2.
![a - 2( - (5)/(11) ) = 4 \\ a + (10)/(11) = 4 \\ a = (34)/(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i2b41cqion7an0bg0lyqdkqdwy8ybpp8o3.png)